THE EUROPEAN BANKING UNION: FEATURES OF THE LEGAL REGULATION OF THE SINGLE SUPERVISORY MECHANISM (INNOVATIVE ECONOMY, 2025)
Patskan V.V.  THE EUROPEAN BANKING UNION: FEATURES OF THE LEGAL REGULATION OF THE SINGLE SUPERVISORY MECHANISMPurpose. The aim of the article is to study the conceptual foundations of the EU Banking Union, to determine its purpose, to analyse the main structural elements of its architecture.Methodology of research. In the course of the study, a set of methods of scientific cognition was used, which made it possible to ensure the consistency and validity of the research. The abstract and logical method was used to summarize information from various sources and create a comprehensive view of the issues under study, to formulate theoretical conclusions and generalizations regarding the specifics of legal regulation of the single supervisory mechanism of the European Banking Union; analysis and synthesis were used to characterize the activities of legal regulation of legal regulation; the monographic method was used for a detailed study of the research results, in particular, the analysis of the regulatory framework. The combination of the aforementioned methods contributed to the achievement of the research objective and fulfilment of all the tasks set out in the logic of modern legal doctrine and taking into account the requirements of the acquis communautaire.Findings. The study analyses the institutional structure and functional content of the European Banking Union (EBU), focusing on the key element of its architecture - the Single Supervisory Mechanism (SSM), which operates under the auspices of the European Central Bank (ECB). The author establishes that the Single Supervisory Mechanism plays a central role in ensuring the stability of the Euro area banking system, in particular, through the concentration of supervisory powers over the largest financial institutions. The author analyses the division of competencies between the ECB and the national supervisory authorities of the member states, which ensures a multi-level system of control over banking activities. The strengths of the Single Supervisory Mechanism are identified, in particular, its independence, centralized approach to decision-making and high level of professional expertise.Originality. The author proves the causal relationship between the formation of the European Banking Union and the increase in the stability of the banking system of the European Union, which, unlike the existing approach, allows for effective unification of supervision and regulation standards, reducing systemic risks. The approaches to analysing the role of the Single Supervisory Mechanism (SSM) were improved, which allowed to reveal the specifics of the dual mandate of the European Central Bank (ECB), which combines centralized coordination of banking supervision with the use of local institutional capacity of national regulators. The concept of integration of supervisory functions was further developed, which contributes to the efficiency of financial crisis management in the face of current challenges.Practical value. The results of the study are of practical value for Ukraine, as they reveal the legal framework and mechanisms of banking supervision within the European Banking Union, which can be used to adapt national legislation to European standards in the process of European integration. The established peculiarities of the ECB's cooperation with national authorities and the mechanism of close cooperation for countries outside the euro area provide Ukraine with a model for harmonizing supervisory practices and strengthening the stability of the banking system. Key words: European Banking Union, banking supervision, European Central Bank, European integration, financial stability.
Keywords: European Banking Union; banking supervision; European Central Bank; European integration; inancial stability